(3CSGSjGJ GdEOGQI GdeGdjIs - (3MeRI eMehO(B, (3GdRHjOjs ((3YeGf(B:s (3GdhQGb ddfTQ hGdJhRjY(B,s, 2006)
(3GdEOGQI GdeGdjI fXQI aj GdeVehf GdYGe(B- (3CgOGa GdEOGQI GdeGdjI(B- (3hXGFa GdEOGQI GdeGdjI(B- (3GdJMdjd GdeGdj(B- (3GdJNWjW hGdQbGHI GdeGdjI(B-(3EOGQI QCS GdeGd GdYGed(B- (3GdEOGQI GdfbOjI hGdESJKeGQjI GdbUjQI GdCLd(B- (3EOGQI GdMSGHGJ GdeOjfI(B- (3EOGQI GdehLhOGJ GdKGHJI(B- (3EOGQI GdJehjd(B- (3GdJehjd GdbUjQ GdGLd(B- (3GdJehjd Whjd GdCLds
Keywords: (3GdEOGQIs; (3GdEOGQI GdeGdjIs